Teaching Material Culture and Chinese Gardens at American Colleges - Li Han (The ASIANetwork Exchange: A Journal for Asian Studies in the Liberal Arts, 2012)
The paper reflects on the experience of designing and teaching a course on material culture and Chinese gardens. Involving traditional philosophy, ethics, religion, painting, calligraphy, craft, literature, architecture and horticulture, a classical Chinese garden can be considered a microcosm of Chinese culture. This essay discusses the textbooks and general organization of the course, particularly focusing on how students study the key elements (rocks, water, plants and architecture) in building a Chinese garden. Some Chinese literature with representations of gardens that can be used for this class is also introduced. In addition, this essay uses two classical Chinese gardens built in the United States (the Astor Court and the Garden of Flowing Fragrance) to discuss the appropriation of “Chinese-ness” in different geographical, physical and cultural environments. Finally, some available online resources and technologies that have enhanced student understanding of the subject matter are introduced.